The hidden costs of automation: does robot adoption affect children’s mental health? - Zou, Yueqing; Wang, Jiaxin; Wang, Liang (Frontiers in Psychology, 2025)
IntroductionIndustrial automation is profoundly transforming the labor market, yet it may also impose hidden costs beyond economic outcomes. In particular, heightened labor market competition caused by robot adoption may create intergenerational costs, such as adverse effects on children’s mental health.MethodsThis study combines survey data from the 2012-2020 China Family Panel Studies with robot data from the International Federation of Robotics to investigate the impact of automation on the mental health of Chinese children. To address endogeneity concerns, we construct an instrumental variable for domestic robot adoption using U.S. robot data and employ a two-stage least squares (2SLS) approach.ResultsThe findings reveal that a one-standard deviation increase in robot adoption (0.414 robots per thousand workers) increases the likelihood of severe depression among Chinese children by 0.75 percentage points. These adverse effects are largely mediated by heightened academic pressure and reduced positive parent-child interactions. Furthermore, the effects are stronger among girls and children living in urban areas.DiscussionThis study advances understanding of the broader social implications of automation. It highlights the often-overlooked psychological costs of automation, demonstrating that its effects extend beyond the current workforce to future generations.